Priority setting in various DG technologies considering the reduction of energy subsidies using FAHP method - Rezakhani, Shadi; Naghdi, Mojtaba; Yousefi, Mohammad; Kia, Nima (2015 20th Conference on Electrical Power Distribution Networks Conference (EPDC), 2015)
Distributed generation is expected to play an increasing role in emerging electric power systems due to spreading of big cities, cost of power networks expansion and placement issues of traditional power plants. Various technologies in distributed generation such as photovoltaic, wind turbines and fuel cells are introduced but due to limitations in energy resources and technical-economical issues, priority setting for these technologies is important. The purpose of this paper is to analyze appeal of distributed generation (DG) technologies assuming energy subsidies has been stopped by the government. This is a subject of multi-criteria decision-making (MCDM) which is proposed to solve by analytic hierarchy process in this paper. Also, fuzzy analytic hierarchy process is implemented for uncertain viewpoints of decision makers. Results show that this method is an effective tool for considering uncertainty in MCDM problems.